Real-time measurement of oxyhemoglobin concentration changes in the frontal micturition area: An fNIRS study - Sakakibara, Ryuji; Tsunoyama, Kuniko; Takahashi, Osamu; Sugiyama, Megumi; Kishi, Masahiko; Ogawa, Emina; Uchiyama, Tomoyuki; Yamamoto, Tatsuya; Yamanishi, Tomonori; Awa, Yusuke; Yamaguchi, Chiharu (Neurourology and urodynamics, 2010)
Objective To explore brain activity in the frontal micturition area during natural bladder behavior. Methods Five control subjects (one man and four women; mean age 61 years [38–70]) and four subjects with detrusor overactivity (all men; mean age 55 years [33–65]) were enrolled in the study. We performed real‐time measurements of oxyhemoglobin concentration (oxy‐Hb) changes in the frontal micturition area using functional near‐infrared spectroscopy (fNIRS) in response to quasi‐natural, continuous bladder filling, and voiding in a sitting position. Results In the control group the following results were obtained: (1) a slight increase of oxy‐Hb before first sensation occurred, (2) there was a continuous increase of oxy‐Hb during bladder filling to the point just after voiding began, (3) there was a continuous decrease of oxy‐Hb after voiding, (4) in subjects who were unable to urinate, oxy‐Hb also decreased after attempting to void, and (5) the area activated was the bilateral lateral prefrontal area, particularly Brodmann's areas 8, 10, and 46. In the detrusor overactivity group, (6) an increase of oxy‐Hb before first sensation was rare and frontal cortical activation was weak, (7) at the moment detrusor overactivity appeared, fNIRS brain activity in the frontal cortex did not change significantly; and otherwise the results were almost the same as those in the control group. Conclusions This study shows that the frontal micturition area is activated during natural bladder filling and voiding using fNIRS. Neurourol. Urodynam. 29:757–764, 2010. © 2010 Wiley‐Liss, Inc.